PENGARUH SISTEM PENILAIAN KINERJA DAN SISTEM REMUNERASI TERHADAP KINERJA PEGAWAI MELALUI MOTIVASI KERJA PADA BADAM PENGELOLA DANA PERKEBUNAN KELAPA SAWIT - Sujatmiko, Tri (JURNAL ILMIAH EDUNOMIKA, 2024)
This study aims to find out whether the performance appraisal system and remuneration system have a partial effect on employee motivation at BPDPKS and to find out if the motivation of HR employees affects employee performance at BPDPKS. The data collection method used in this study was documentation and questionnaires collected by distributing questionnaires to all BPDPKS officials and employees as many as 84 employees.There are three steps of this research analysis stage: the first stage is a descriptive analysis of the characteristics of the respondents describing based on age range, education and gender, the second stage is a descriptive analysis of research variables looking at the description of the research variables based on the respondent's point of view and the third stage is the SEM PLS analysis carried out to assess the variable influence test with 2 (two) stages, namely the outer model test and the inner model test. The results of the SEM PLS analysis stated that the composition of remuneration had no effect on employee work motivation, the performance appraisal system had a good and large influence on work motivation, employee motivation was influenced by the performance appraisal method and remuneration composition at the same time and employee performance was positively and significantly influenced by work motivation